La Inteligencia Artificial: Retos, Tendencias y su interrelación con el Sistema de Propiedad Intelectual Mexicano desde una visión Humanista - Gorches G., Esteban C. (2025)
This article examines the challenges and trends of Artificial Intelligence (AI) from an international and national legal perspective, focusing on relevant cases in Mexico and around the world. It analyzes the current legal framework and its interpretation, emphasizing the importance of considering AI as a tool whose responsibility lies with its users. Additionally, it explores the Human Rights involved and the legal capacity of AI in terms of rights and obligations, highlighting some judicial precedents in Mexico. The article aims to provide, as far as possible, a comprehensive view of how different branches of law must adapt and evolve in response to the advancement of AI.